A strategy to assess water meter performance - Cordeiro, Clara (2022)
A recurring problem that troubles water companies is that of timely detection of malfunctioning water meters. Indeed, defective water meters impair the management of water supply and diminish water companies’ revenues. The management of nonrevenue water (NRW) is one key issue for improving water use efficiency, reducing gaps between water supply and demand (Ncube and Taigbenu 2019). Water losses in the distribution system can be categorized as either real (leakage) or apparent (commercial) losses (Mutikanga et al. 2011). Water meter under-registration resulted in apparent losses and lost revenue (Moahloli et al. 2019; Fourie et al. 2020), being apparent losses one of the components of NRW. As Criminisi et al. (2009) explain, apparent losses are caused by unauthorized consumption and meter inaccuracies, corresponding not to physical but rather to financial losses. Since they are water volumes taken from the network and consumed but not accounted for, as a consequence, the company will be jeopardized by the unaccounted water volume, resulting in an important impact on the utility’s water and economic balances. A long-known fact is that reducing apparent losses caused by meter inaccuracies can result in substantial short-term increases in utility revenue and lead to increasingly equitable service charges for long-term water consumers (Richards et al. 2010; Kadenge et al. 2020). The accurate measurement of the water collected by meters is crucial in reducing any uncertainty affecting the water balance and has significant technical and economic implications (Pacheco et al. 2020). A cubic meter consumed but not measured reduces the company revenue in quantity equal to the selling price of the last cubic meter of water consumed by that consumer (Arregui et al. 2018). The water companies’ awareness for the responsible use of water has gained importance, with climate changes emphasizing this need. In the context of water scarcity, Oviedo-Ocana et al. ˜(2020) alert to the importance of assessing losses in water distribution systems since the compensation of water losses represents an increase in the source’s water supply. Enhancing that water use efficiency and conservation are priority alternatives to ensure, for example, universal access to drinking water and reducing the number of people suffering from water scarcity. Furthermore, Pacheco et al. (2020) emphasize that water measurement will become an even more critical aspect in the near future because of the increase in the world’s water supplies due to population growth. In this context, one form of water companies to be aware of its important role is to steer the effective water consumption and guarantee an efficient manutention of its equipment, namely the water meters. Current research confirms that several factors affect a water meter’s accuracy, particularly water meterage and total registered volume (Moahloli et al. 2019; Pacheco et al. 2020). Detecting the point in time in which water meters should be replaced implies that they can be substituted proactively to minimize the impact of water consumption nonregistration and under-registration on NRW (Moahloli et al. 2019). There seems to be no specific determination and/or agreement on a water meter lifespan or optimal replacement period. Water meter producers only give a limited warranty against manufacturing defects but do not specify the meters’ lifetime (Moahloli et al. 2019). It is believed that the premature replacement of water meters will result in a higher average life-cycle cost due to the initial fixed costs. However, if a meter is replaced too late, a significant loss of revenue caused by meter nonregistration and under-registration will also increase the average life-cycle cost (Fontanazza et al. 2015). The main studies on this problem have adopted approaches based on laboratory studies, which may implicate two significant issues: (1) the high costs inherent to the laboratory, and (2) the conditions in which the tests are taken upon are far from the real scenario.